Chile - Zonas Extremas Policies and Beyond : An Assessment of Costs and Impact with Recommendations of Avenues for Policy Reform - World Bank (Washington, DC, 2012)
In Chile, certain areas have historically been identified as Extreme Zones - Zonas Extremas (ZE) and qualified as such, have received special treatment in terms of public policies. Most of the exception instruments that currently benefit the ZE were created more than 20 years ago, and have followed an incremental dynamic, not based on impact assessments. This has generated a wide range of benefits, some of doubtful effectiveness and efficiency, with significant fiscal costs, and with diverse objectives that are not necessarily consistent. In addition, Chile has experienced considerable change since these policies were established, altering the conditions that initially justified some of them. Among the changes are greater decentralization, greater democratization - both at the national and local levels - opening and internationalization of the economy, social progress, and development of human capital. This study intends to develop guidelines for a comprehensive regional development policy for balanced long-term, and equitable growth, both at the interregional level-encompassing all the regions-and at the population level-with emphasis on targeting public efforts to the poorer population. Thus, the study will contribute to estimate the fiscal cost of the pro-ZE policies; to evaluate the effectiveness and efficiency of current ZE policies; and, to propose guidelines for a comprehensive regional development policy. To this end, the study pursues specific objectives: characterization and discussions on the qualification of ZEs; analysis of the consistency of current ZEs public policies; scaling of fiscal expenditure (subsidies) and tax-related (exemptions) that such policies imply; qualitative evaluation of its performance in terms of declared objectives; quantitative evaluation of performance in terms of economic and social impact; determination of effectiveness and efficiency; identification of best practices and international instruments in achieving similar objectives; and, proposal of guidelines for the reformulation, elimination and creation of instruments.